Madelung’s disease -a case series from a single-center experience - Łącka, Monika; Wojciechowska, Julia; Bernecka, Paulina; Szóstek, Hanna; Stolp, Amelia; Zieniewicz, Zuzanna; Miller, Martyna; Ossowska, Brygida; Jankau, Jerzy (Frontiers in Surgery, 2025)
IntroductionMadelung's disease (MD), also known as multiple symmetric lipomatosis, is a rare metabolic disorder characterized by the accumulation of unencapsulated adipose tissue, predominantly in the head, neck, and upper trunk. Non-surgical treatment options remain limited in effectiveness, making surgical excision the primary therapeutic approach. However, challenges such as intraoperative bleeding and postoperative recurrence necessitate ongoing refinement of surgical techniques.MethodsWe conducted a retrospective case series involving six patients diagnosed with Madelung's disease and treated surgically between 2018 and 2024 at the Department of Plastic Surgery, University Clinical Hospital in Gdańsk. All patients underwent staged surgical excision of pathological adipose tissue following infiltration with Klein's solution to minimize bleeding. Demographic and clinical data, comorbidities, fat distribution patterns (Type I or II), and body mass index (BMI) were recorded. The primary outcome was recurrence in the operated regions over a one-year follow-up period; the secondary outcome was the occurrence of surgical complications.ResultsThe study included five male and one female patient, with a mean age of 57 years (range: 44–67). Risk factors included smoking (n = 4), alcohol abuse (n = 2), and metabolic or systemic comorbidities. The BMI ranged from 21 to 33. All patients underwent successful surgical resection, with no recurrence of adipose tissue in the treated areas during follow-up. Histopathological evaluation confirmed the presence of benign lipomas in all specimens. No major complications, such as excessive bleeding or postoperative infections, were observed.DiscussionSurgical excision with prior infiltration of Klein's solution appears to be a safe and effective treatment for Madelung's disease, offering low recurrence and complication rates. The use of staged procedures and careful intraoperative management is critical in addressing the disease's vascular and infiltrative nature. While these findings are promising, larger prospective studies are needed to validate the efficacy of this approach and to further optimize surgical strategies for this rare condition.